Chitinolytic activities in the gut of Aedes aegypti (Diptera : Culicidae) larvae and their role in digestion of chitin-rich structures - Souza-Neto, J. A.; Gusmao, D. S.; Lemos, FJA (Elsevier B.V., 2003)
Mosquito larvae are believed to be capable of digesting chitin, an insoluble polysaccharide of N-acetylglucosamine, for their nutritional benefit. Studies based on physiological and biochemical assays were conducted in order to detect the presence of chitinase activities in the gut of the detritus-feeding Aedes aegypti larvae. Larvae placed for 24 h in suspensions of chitin azure were able to digest the ingested chitin. Semi-denaturing PAGE using glycol chitin and two fluorogenic substrate analogues showed the presence of two distinct chitinase activities: an endochitinase that catalyzed the hydrolysis of chitin and an endochitinase that cleaved the short substrates [4MU(GlcNAc)(3)] and [4MU(GlcNAc)(2)] that hydrolyzed the chitobioside [4MU(GlcNAc)(2)]. The endochitinase had an extremely broad pH-activity against glycol chitin and chitin azure, pH ranging from 4.0 to 10.0. When the substrate [4MU(GlcNAc)(3)] was used, two activities were observed at pH ranges 4.0-6.0 and 8.0-10.0. Chitinase activity against [4MU(GlcNAc)(3)] was detected throughout the gut with the highest specific activity in the hindgut. The pH of the gut contents was determined by observing color changes in gut after feeding the larvae with color indicator dyes. It was observed a correlation between the pH observed in the gut of feeding larvae (pH 10-6.0) and the optimum pH for gut chitinase activities. In this work, we report that gut chitinases may be involved in the digestion of chitin-containing structures and also in the partial degradation of the chitinous peritrophic matrix in the hindgut. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: chitinase; chitin; digestive enzyme; peritrophic matrix; Aedes aegypti; gut pH; substrate specificity